The effect of hank’s balanced salt solution (HBSS) storage time on transdentinal diffusion in extracted third molars - Araya, Francisco; Sommariva, Claudia; Moncada, Gustavo; Cartagena, Álvaro; Letelier, Claudia; Oliveira-Junior, Osmir; Martín, Javier; Fernández, Eduardo (Revista Facultad de Odontología Universidad de Antioquia, 2014)
Introduction: the solution used to store dentin disks while being studied has proven to be vital in reproducing possible “in vivo” conditions, and it is ultimately critical in evaluating hydraulic conductance studies. The goal of this in vitro study was to determine transdentin filtration rate variation in human dentin disks after 2, 4, 6, 7, 14, 21, and 28 days stored in Hank’s Balanced Salt Solution (HBSS), 10% formalin, and saline solution. Methods: this study included 41 unerupted healthy human third molars. These teeth were disinfected in 0.1% thymol for 24 hours before being embedded in epoxy resin blocks and then cut to obtain 1 mm thick dentin disks. The disks’ hydraulic conductance was later measured, and then they were separated and stored in different solutions. They were sorted out in three groups: a) 10% formalin, b) Hank solution (HBSS) and c) saline solution. Hydraulic conductance was measured after 1, 2, 4, 6, 7, 14, 21, and 28 days. Statistical analysis was performed by ANOVA and Tukey’s post hoc (SPSS v.15). Results: the results suggest that the average of dentine disks’ hydraulic conductance increased in all the storage solutions when comparing the analysis between day 1 and day 28. Conclusions: no significant differences were found (p > 0.005) in terms of hydraulic conductance among the various times the disks were stored in Hank’s solution.